"Are chemistry educational apps useful?" – a quantitative study with three in-house apps. Issue 1 (27th September 2017) - Ping, Grace Lee Yuan; Lok, Chang; Wei Yeat, Tan; Cherynn, Tan Jie Ying; Tan, Emelyn Sue Qing
Abstract : Three internally developed mobile apps, "3D Sym Op", "SM2 Chem" and "ARMolVis", available for free on both the Apple App Store and Google Play Store were evaluated in seven studies. Each study was a systematic process of Pre-Test, In-lecture App Demo, App Assisted Interactive Tutorials (AAITs) and/or Independent App Usage (IAU), followed by a Survey and Post-Test. Overall, the mobile apps were effective evident by the higher Post-Test vs. Pre-Test % increase for those who used the app more frequently compared to those who used the app rarely. Apps were most effective when used in AAITs with the Blended Learning approach. This approach requires the physical presence of both teacher and student, but with some element of student free play such as using the app to complete worksheets in pairs or groups.